Nando's chilli sourcing : innovation for social impact - Urban, Boris; Hobbs, Jacklynne (London : Wits Business School, 2015)
In late 2013, Nando's, a global chicken restaurant chain, marked the successful implementation of a project for ethical sourcing of African bird's eye chillies (ABE) - the signature ingredient of the brand. The initiative had set Nando's on the road to securing its annual requirement of ABE from traceable sources, while improving the lives of participating small-scale farmers in Mozambique and Zimbabwe. However, Jed Goldstein, programme manager of the initiative, wondered whether Nando's could sustain ethical sourcing of ABE in a context where procurement of other goods and services continued unchanged.
Originally published in Urban, B., & Hobbs, J. (2015). Nando's Chilli sourcing: Innovation for social impact. WBS-2015-13. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Goldstein, Jed; Hot peppers -- Africa -- Case studies; Entrepreneurship -- Case studies